Evaluation of Study Skills in Nursing Students (International Journal of Nursing Education, 2019)
Introduction:- There are large number of modification in students study style specifically when they begin college life. On some occasion students found that technique they used for studying in schooling which not every time productive in college. Many time Students may face difficulties to learn the content which is delivered, not because they aren’t studying, but because there is requirement to understand in different way to gain.1 The purpose of this research is to explain information which handled effective contribution of study skills to academic competence, and to identify better strategies that are effective in helping students to improve their study skills. Method: in this descriptive cross-sectional study questionnaires were distributed among all B.sc. Nursing students. Total 51 questionnaire containing to assess study skills. A questionnaire was assessed in six critical study skills which considering text book reading, note taking, memory, test preparation, concentration, and time management. At the conclusion of the inventory, each of these skills assessed based on the manner in which the questions were answered. The permission taken from South Central College Chicago to use “Study Skills Inventory.2 Result - The highest need for change in the study skills was found in the area of time management skills with 59.5% followed by 43% in note taking skills, 34% in text book reading skills, 23.5% in concentration skills, 20% in memory skills and 15.5% in test preparation skills. Whereas statistically The p value 0.35 is greater than the 0.05 it shows there is no significant relationship between study skills and percentage obtained among nursing students, r( 198) = 0.067, p=0.35. Conclusion: This study finds some empirical evidence to the body of knowledge of study skills of Nursing students. It appears that students possess better status in test preparation. The results of this research may be useful for college and university nursing program administrators, educators, tutors, and students.
Keywords: –(Study skill Inventory, Nursing Students ,Nursing college, Study skills and Academic performance)